2015
DOI: 10.1103/physrevlett.114.013601
|View full text |Cite
|
Sign up to set email alerts
|

Route to Chaos in Optomechanics

Abstract: We establish the emergence of chaotic motion in optomechanical systems. Chaos appears at negative detuning for experimentally accessible values of the pump power and other system parameters. We describe the sequence of period-doubling bifurcations that leads to chaos and state the experimentally observable signatures in the optical spectrum. In addition to the semiclassical dynamics, we analyze the possibility of chaotic motion in the quantum regime. We find that quantum mechanics protects the optomechanical s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
107
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(117 citation statements)
references
References 38 publications
(62 reference statements)
8
107
0
2
Order By: Relevance
“…In particular, one can strong driving the cavity so that the OMS enters into a regime of self-induced oscillations [9][10][11][12], where the backaction-induced mechanical gain overcomes mechanical loss. Further increasing the strength of the driving laser, chaotic motion emerges both in the optical and mechanical modes requiring no external feedback or modulation [13][14][15][16]. It is useful for generating random numbers [18] and implementing secret information processing [19][20][21].…”
mentioning
confidence: 99%
“…In particular, one can strong driving the cavity so that the OMS enters into a regime of self-induced oscillations [9][10][11][12], where the backaction-induced mechanical gain overcomes mechanical loss. Further increasing the strength of the driving laser, chaotic motion emerges both in the optical and mechanical modes requiring no external feedback or modulation [13][14][15][16]. It is useful for generating random numbers [18] and implementing secret information processing [19][20][21].…”
mentioning
confidence: 99%
“…Moreover, as predicted in ref. 9 for sufficiently high laser power, the system can eventually enter into a chaotic regime, which may be exploited for chaos-based secure data communication or sensing, among other applications. In this regard, integrated OM systems may present advantages with respect to coupled lasers10 or hybrid optoelectric oscillators11 in terms of the ease of integration, scalability and engineering of the nonlinearities12.…”
mentioning
confidence: 99%
“…Self-sustained oscillations occur for amplitudes A where the power balance between gains from the radiation pressure (P rad = P |α| 2 Imβ avg) and losses due to friction (P fric =Γ |β| In case (a), the two innermost orbits have amplitudes A1 ≈ 1.2 and A2 ≈ 2.7. In cases (b), (c) the innermost orbit shows a few period doubling bifurcations that occur on the route to chaos [11], in case (d) it is chaotic. Now introduce the five dimensionless parameters [5,6] …”
mentioning
confidence: 99%
“…In a previous paper [11] we observed that the classical dynamical patterns, which are characterized by the multistability of self-sustained oscillations, change in a characteristic way if one moves into the quantum regime. Previously stable orbits become unstable, the system oscillates at a new amplitude, and especially the classical chaotic dynamics is almost immediately replaced by simple periodic oscillations.…”
mentioning
confidence: 99%
See 1 more Smart Citation